Boom in Arabic-English literary translation: A contextual analysis of geopolitics and patronage (2003-2020) - Al-Ramadan, Raidah; Sayaheen, Bilal; Malkawi, Mona (Research Journal in Advanced Humanities, 2025)
This paper explores the boom in Arabic-English literary translation from 2003 to 2020. It hypothesizes that geopolitics and patronage have a major role in shaping the landscape of literary translation from Arabic, with geopolitics playing a more dominant role. The research is based on a corpus of 655 Arabic literary works translated into English in the period between 2003 and 2020, compiled from various online resources. The data is analyzed in terms of each country’s contribution and the timeline of the translations. A contextualization of these translations is then provided by discussing political events and patronage initiatives in relation to the translated works. The analysis reveals a strong correlation between the patterns of translation from Arabic into English and regional politics and patronage, suggesting that they have sparked a surge of interest in Arabic literature among English-speaking audiences.